Are free-living nematodes effective environmental quality indicators? Insights from Bohai Bay, China. (August 2021) - Hua, Er; Zhu, Yanmei; Huang, Deming; Liu, Xiaoshou
Highlights: Metals concentrations played a key role in influencing nematodes in Bohai Bay. Use of nematodes as indices of environmental quality status was assessed. Nematode features were sensitive to deteriorations in ecological quality. Nematode features were effective in highlighting the worst quality status. Abstract: Free-living marine nematodes are sensitive biological indicators of environmental quality in marine sediments. This study investigated nematode communities in coastal waters in Bohai Bay, China. Nematode community taxonomic structure, colonizer–persister classes, maturity index (MI), index of trophic diversity (ITD), Shannon–Wiener diversity index ( H′ ), together with the Hakanson's Ecological Risk Index, were applied to assess the environmental quality of the investigated stations. The taxonomic structure, MI, ITD, and H′ varied among the study stations. In addition to the stochastic causes, variability in environmental variables together with metal concentrations explained, to a certain extent, the observed variations in nematode features. The differentiation in nematode species' composition was attributed to changes in water depth, temperature, salinity, dissolved oxygen concentration, sediment medium diameter, organic matter, chlorophyll-a and pheophytin-a concentrations, and concentrations of manganese (Mn) and cobalt (Co). Mn was the most influential metal in explaining nematode diversity. MI appeared to be affected more by metals than by other environmental variables. According to the nematode features, the environmental quality ranged from bad to good at the majority of stations, although the rankings varied among different indices. Taxonomic structure, life strategy traits, ITD, and H′ were all effective in highlighting the areas subjected to severe metal contamination in the bay, and could provide more comprehensive assessments when used in combination. These indices suggested a more severe pollution status than the results obtained from the Hakanson's Ecological Risk Index method, and may be more sensitive to ecological quality deterioration. However, their effectiveness requires further testing over larger spatial ranges and with more data.